Speech And Language Delay Or Disorder In Children Associated With Epilepsy - Ilhamsyah, Nugraha -; Sinaga, Nurcahaya - (Buletin Farmatera, 2025)
Abstract: Speech and language disorders are common clinical features often associated with neurodevelopmental disorders. Abnormal brain activity associated with epilepsy can impact the developmental trajectory of cognitive processes, such as language. Early identification of children with speech and language delays and disorders will allow for early intervention before learning and behavioural problems develop to achieve better academic and social outcomes. This study evaluates whether children with epilepsy experience speech and language disorders. Observational analysis with a cross-sectional study with patient medical record data in the outpatient clinic of a pediatric neurology consultant from January 2023 to February 2025. Risk factors were analysed bivariate and multivariate. This study found that out of 479 children with epilepsy, 331 or 62.7% experienced speech and language delay or disorders. The study concludes that a significant proportion of children with epilepsy (62.7%) experience speech and language disorders. The presence of these disorders is notably associated with a higher frequency of seizures before treatment and the existence of comorbid conditions.